2019
DOI: 10.1037/cep0000180
|View full text |Cite
|
Sign up to set email alerts
|

Freely-selected and forced-choice responses bind with relevant object-occupied locations in visuospatial tasks.

Abstract: Past work has shown that cued manual responses in visuo-identity tasks bind to irrelevant stimulus features, present at the time these responses were executed (prime trial). These response bindings manifested their existence via impacts on later related processing (probe trial). Here, we extended this prior research by showing that response binding is likely a pervasive processing characteristic. We saw that uncertain prime-trial responses (i.e., free-choice, forced-choice) did bind to the relevant "location" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Recently, Kajaste and Buckolz (2017) extended the earlier binding results produced with visual identity tasks to visual location-based tasks, where the relevant feature of the designated target object determining response selection is its spatial position. Specifically, Kajaste and Buckolz demonstrated that during the course of prime trial processing, the selected response binds to the relevant location occupied by the prime target object and, less consistently, to the irrelevant target's identity.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, Kajaste and Buckolz (2017) extended the earlier binding results produced with visual identity tasks to visual location-based tasks, where the relevant feature of the designated target object determining response selection is its spatial position. Specifically, Kajaste and Buckolz demonstrated that during the course of prime trial processing, the selected response binds to the relevant location occupied by the prime target object and, less consistently, to the irrelevant target's identity.…”
Section: Introductionmentioning
confidence: 87%